Landasan Filosofis dan Relevansinya Terhadap Kajian Keislaman - Firdaus Akbar (Journal Khafi : Journal Of Islamic Studies, 2023)
In the early centuries of the emergence of Islam, Muslims in carrying out Islamic shari'a only relied on the Qur'an and Hadiths which were explained and taught by the Islamic scholars themselves. So that in lecturing and explaining the meaning of the Qur'an and Hadith they still use the basics of knowledge born by Islamic scholars themselves such as the science of Fiqh, Tafsir, Asbab An-Nuzul, and others. The philosophical approach tries to reach universal conclusions by examining the root of the problem. This method is fundamental in a radical and integral way, because it discusses something in terms of essence (the essence of something). Referring to the above frame of mind, in this research the author tries to explain the general picture of the study of philosophy in the Islamic approach